1999
DOI: 10.1093/molehr/5.2.139
|View full text |Cite
|
Sign up to set email alerts
|

Heparin inhibits proliferation of myometrial and leiomyomal smooth muscle cells through the induction of alpha-smooth muscle actin, calponin h1 and p27

Abstract: Mast cells are widely distributed in human tissues, including the human uterus. However, the function of mast cells in uterine smooth muscle has not been clearly established. Mast cells possess secretory granules containing such substances as heparin, serotonin, histamine and many cytokines. To help establish the role of mast cells in the human myometrium, the action of heparin was investigated using smooth muscle cells (SMC) from normal myometrium and from leiomyoma. The proliferation of cultured myometrial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 37 publications
2
22
0
1
Order By: Relevance
“…30 These data suggest that heparin inhibition of SMC proliferation probably involves several different pathways. Our study revealed that the CDK inhibitor p27 plays a critical role in mediating the antiproliferative property of heparin on hypoxia-induced pulmonary hypertension and remodeling, but p21 does not.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…30 These data suggest that heparin inhibition of SMC proliferation probably involves several different pathways. Our study revealed that the CDK inhibitor p27 plays a critical role in mediating the antiproliferative property of heparin on hypoxia-induced pulmonary hypertension and remodeling, but p21 does not.…”
Section: Discussionmentioning
confidence: 88%
“…Heparin inhibition of SMC proliferation has been associated with several factors including the suppression of c-fos and c-myc, 26 inhibition of the EGF receptor, 27 nitric oxide synthesis, 28 protein kinase activity, 29 modulation of cytosolic calcium, 30 inhibition of the Na ϩ /H ϩ exchanger, 19,25 as well as an increase in p21 11 and p27. 30 These data suggest that heparin inhibition of SMC proliferation probably involves several different pathways.…”
Section: Discussionmentioning
confidence: 99%
“…18 Overexpression of CNN1 could suppress SMC proliferation and neointima formation. 19,20 The X-box-binding protein 1 (XBP1) was originally identified as a stress-inducible transcription factor in both invertebrate and vertebrate cells, and essential for cell survival under stress conditions. [21][22][23] Under ER stress conditions, XBP1 mRNA undergoes unconventional splicing through an ER-resident kinase that possesses ribonuclease activity, the inositol-requiring enzyme 1 α (IRE1α).…”
mentioning
confidence: 99%
“…Heparin acts as an anticoagulant and is thought to stimulate angiogenesis [8]. Heparin proteoglycan, released by activated mast cells, inhibits the proliferation of smooth muscle cells in arterial tunica media and uterine myometrium [9,10].…”
Section: Brief Characteristics Of the Mast Cell And Its Role For Smoomentioning
confidence: 99%
“…It was demonstrated by [9] the inhibitory effect of heparin on human myometrium proliferation, suggesting that it could induce the differentiation of uterine smooth muscle cells and to influence tissue remodelling and reconstruction in different physiological and pathophysiological events.…”
Section: Heparinmentioning
confidence: 99%